Comparative assessment of the outdoor thermal environment and evaluation of urban heat island mitigation strategies for urban areas in poblacion district, Davao City - Tubidan, Glynry L.; Ylagan, Myrafe S. (2023)
Due to the alarming rate of urbanization in Davao City?s Central Business District, the outdoor thermal environment is compromised. This phenomenon is accompanied by the occurrence of urban heat islands (UHI). The first objective of the study is to evaluate the existing outdoor thermal environment of urban areas in the Poblacion District where there are six study sites selected. Among all the sites, Site 6 (City Hall Complex)has the highest THI value (average THI=26.81°C, peaks at 4:00pm=30.63°C). Site 6 was then chosen as a control variable (SC0) for Scenario Simulation which covers the second objective is to determine how to improve the existing outdoor thermal environment of these areas by incorporating various mitigation strategies. All these are made possible through 3D simulation using the ENVI-met software. Among the individual scenarios tested, SC2 which involves improvement of material albedo averaged the highest THI difference (0.37°C; range=0.07°C - 0.83°C), followed by SC1 which involves improvement in vegetation (0.29°C; range=0.08°C - 0.74°C). Lastly, SC3 involving green roofs has the least average THI difference (0.29°C; range=0.08°C - 0.74°C) denoting that this mitigation strategy is substantially less effective compared to the other two scenarios. Among the all combination scenarios tested, the SC5 which combines all the mitigation strategies has the best result (0.67°C; range=0.24°C - 1.33°C). SC4 that involves mitigation strategies from SC1 and SC2 also showed a great result (0.47°C; range=0.07°C - 0.99°C).
Thesis (BS Architecture)--University of the Philippines Mindanao, 2023